Rainbows of Resistance : LGBTQ Pride Parades Contesting Space in Post-Conflict Belfast - Drissel, David (My University, 2017)
The article seeks to demonstrate how marchers in the annual LGBTQ Pride Parade strategically contest and reclaim heteronormative public spaces in Belfast, Northern Ireland. There is an exploration of participants adapting transnational symbolic representations and discourses to the distinct national-local cultural milieu in which they are scripted and performed. The discursive frames, symbols, and performances of Belfast Pride are compared to those of sectarian parades in the city. The subaltern spatial performances and symbolic representations of Belfast Pride are depicted as confronting a universalized set of heteronormative discourses involving sexuality and gender identity, while at the same time contesting a particularized set of dominant local-national discourses related to both ethnonational sectarianism and religious fundamentalism in Northern Ireland.
Keywords: 306 Kultur und Institutionen; Belfast; Northern Ireland; LGBTQ Pride Parade; public space; heteronormativity; sectarianism